Associations of plaque morphology and location with Intraplaque neovascularization in the carotid artery by contrast-enhanced ultrasound imaging - Gu, Shi-Yao; Zhang, Lu-Ni; Chen, Jing; Li, Fang; Yao, Ming-Hua; Jia, Cai-Xia; Wu, Rong (Frontiers in Neurology, 2023)
Objective Intraplaque neovascularization (IPN) is a known indicator of plaque vulnerability, and is thus considered a predictor of stroke. The morphology and location of the carotid plaque may be correlated with plaque vulnerability. Therefore, our study aimed to examine the associations of carotid plaque morphology and location with IPN. Methods A total of 141 patients with carotid atherosclerosis (mean age, 64.99 ± 10.96 years) who underwent carotid contrast-enhanced ultrasound (CEUS) between November 2021 and March 2022 were retrospectively analyzed. IPN was graded according to the presence and location of microbubbles within the plaque. The association of IPN grade with carotid plaque morphology and location was evaluated using ordered logistic regression. Results Of the 171 plaques, 89 (52%) were IPN Grade 0, 21 (12.2%) were Grade 1, and 61 (35.6%) were Grade 2. IPN grade significantly associated with both plaque morphology and location, with higher grades observed among Type III morphology and common carotid artery plaques. Significant negative association was further shown between IPN grade and serum high-density lipoprotein cholesterol (HDL-C) level. Plaque morphology and location, and HDL-C remained significantly associated with IPN grade after adjusting for confounding factors. Conclusion The location and morphology of carotid plaques were significantly associated with the IPN grade on CEUS, and therefore show potential as biomarkers for plaque vulnerability. Serum HDL-C was also identified as a protective factor against IPN, and may play a role in the management of carotid atherosclerosis. Our study provided a potential strategy for identification of vulnerable carotid plaques and elucidated the important imaging predictors of stroke.